Resetting the gut-brain axis in AN: the promise and pitfalls of FMT - Mahnoor Sheikh; Dua Ali Gul; Khadija Imran Siddiqui; Zahra Ishtiaq Hussain; Rohma Zubairi (Intercontinental Journal of Internal Medicine, 2026)
Anorexia nervosa (AN) is a severe psychiatric disorder associated with high morbidity, mortality, and limited therapeutic options. Increasing evidence suggests that alterations in the gut microbiota and disruptions of the microbiota–gut–brain axis may contribute to the pathophysiology of AN by influencing appetite regulation, metabolism, and neuropsychiatric function. Fecal microbiota transplantation (FMT), which involves the transfer of gut microbiota from a healthy donor to a recipient, has emerged as a potential microbiome-based intervention aimed at restoring microbial balance and improving clinical outcomes. Preliminary studies have demonstrated improvements in gut microbial diversity, gastrointestinal function, and weight-related outcomes following FMT in individuals with AN. However, current evidence remains limited, with most data derived from animal models, case reports, and small pilot studies. Significant challenges include the lack of standardized treatment protocols, uncertain long-term safety, and ethical concerns regarding use in vulnerable populations. While FMT represents a promising avenue for future research, robust randomized controlled trials are required to establish its efficacy, safety, and role in clinical practice. At present, FMT should be regarded as a complementary investigational approach rather than a standard treatment for anorexia nervosa.